Multi-modality sparse representation-based classification for Alzheimer's disease and mild cognitive impairment. Issue 2 (November 2015) - Xu, Lele; Wu, Xia; Chen, Kewei; Yao, Li
Highlights Multi-modality classification on 113 AD, 110 MCI patients and 117 normal controls. Originally single-modality SRC was extended as a multi-modality framework (wmSRC). The wmSRC performed better than each single-modality based SRC method. The wmSRC performed better or equally well compared to MKL, RF and JRC.